2022
DOI: 10.1002/app.52789
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of anisotropic PLA/CNT nanocomposites by hot and cold rolling processes for improving mechanical and conductive properties

Abstract: Poly(lactic acid) (PLA) is one of the most important biodegradable polymers, however, brittleness severely limits its applications. Thus, strengthening and toughening PLA is a cutting‐edge research for both academia and industry. In this study, rolling process was applied to simultaneously improve the toughness and strength of PLA and its nanocomposites by regulating microstructure of PLA molecular chains. Results showed that crystallinity and orientation of rolled PLA and its nanocomposites were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…12 Extensive research has been done for improving as well as tuning the physical and mechanical properties of PLA, which usually involves the addition of nanoparticles or blending with another polymer. [13][14][15][16][17][18] In a research conducted by Kim et al, they found that upon adding a small amount of carbon nanotubes/graphene oxide hybrid nanoparticle system, the permeability of oxygen into PLA film would be greatly reduced. 5 Urquijo et al observed that the percentage of gas penetration into a blend of PLA and poly (ε-caprolactone) could significantly be reduced by adding an appropriate amount of nanoclay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Extensive research has been done for improving as well as tuning the physical and mechanical properties of PLA, which usually involves the addition of nanoparticles or blending with another polymer. [13][14][15][16][17][18] In a research conducted by Kim et al, they found that upon adding a small amount of carbon nanotubes/graphene oxide hybrid nanoparticle system, the permeability of oxygen into PLA film would be greatly reduced. 5 Urquijo et al observed that the percentage of gas penetration into a blend of PLA and poly (ε-caprolactone) could significantly be reduced by adding an appropriate amount of nanoclay.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been done for improving as well as tuning the physical and mechanical properties of PLA, which usually involves the addition of nanoparticles or blending with another polymer 13–18 . In a research conducted by Kim et al, they found that upon adding a small amount of carbon nanotubes/graphene oxide hybrid nanoparticle system, the permeability of oxygen into PLA film would be greatly reduced 5 .…”
Section: Introductionmentioning
confidence: 99%